EFL Classes Must Go Online! Teaching Activities and Challenges during COVID-19 Pandemic in Indonesia - Arief Eko Priyo Atmojo; Arif Nugroho (UIN Salatiga, 2020)
In view of the COVID-19 pandemic and government policy to carry out online learning, the present research is aimed at investigating how EFL teachers carry out online EFL learning and its challenges. 16 EFL teachers volunteered to participate in this research through invitation. The EFL teachers were requested to make written reflections regarding their practices in carrying out online EFL learning and the challenges they encounter. Five of them were involved in a follow-up interview individually. Semi-structured interview was administered. Data coding was done and appropriate extracts were informed in results section. To validate the data, data coding was done independently by both researchers, continued by several cycles of discussion. As results, the EFL teachers have carried out online learning through a series of activities ranging from checking the students’ attendance to giving score on the students’ works synchronously or asynchronously depending on each school policy. Various applications and platforms ranging from learning management system to additional resource are employed. However, many problems emerge from the students, the teachers, and the students’ parents along with the valid reasons. Therefore, the online learning does not run well since it lacks of preparation and planning. Implications for better online learning are discussed. Future prospective researches are directed and encouraged. Keywords: COVID-19, EFL teachers, online EFL learning, technology enhanced language learning, technology in language learning.